The Influence of Balanced Scorecard Implementation and Financial Literacy On Msme Performance: A Literature Review - Mangalindung, Giovani Huiser; Hendayana, Yayan (Dinasti Publisher, 2025)
This article examines the effect of the implementation of the Balanced Scorecard and financial literacy on the performance of Micro, Small, and Medium Enterprises (MSMEs). Using a systematic analysis in the form of a literature review from recent studies, this article reveals that the Balanced Scorecard and financial literacy significantly contribute to improving the performance of MSMEs. The Balanced Scorecard provides a comprehensive framework for performance measurement through four perspectives: finance, customer, internal processes, and learning & growth, enabling MSMEs to translate strategies into operational actions. Financial literacy empowers MSME owners with essential knowledge in financial management, including budgeting, savings, credit management, and investment decisions. This article identifies research gaps in the integrated implementation of the two concepts and proposes future research directions. The findings show that the combination of strategic performance measurement tools with increasing financial literacy creates a synergistic effect on the sustainability and competitiveness of MSMEs. This article contributes to management theory by bridging the Resource-Based View and strategic management perspectives, while offering practical implications for policymakers and practitioners of MSMEs.